Archimorficzne i neomorficzne cechy czaszki: analiza interkorelacji - Bielicki, Tadeusz; Miszkiewicz, Brunon (Polskie Towarzystwo Antropologiczne, 1987)
Different regions ot the human cranium, as well as different aspects of its shape, are largely independent of each otherwith regard to the degree of' Deomoiphkm orarchimorphisin. Pronounced prognathism may be accompanied as well by a massive as by a gracile facial skeleton, a braincase large relative to facial size may be accompanied aa well by a rounded as by a sharply angullated occiput, etc. Thus, fossil hominid skulls showing various mosaic combinations of archaic and moderm features are to be expected, at every stage of evolution, simply as products of normal within-population variation.
Archimorphic and neomorphic skull traits: analysis of intercorrelation